Consumer Price Index Manual : Theory and Practice. (Manuals and Guides, 2009)
The consumer price index (CPI) measures the rate at which the prices of consumer goods and services are changing over time. It is a key statistic for economic and social policymaking and has substantial and wide-ranging implications for governments, businesses, and households. This important and comprehensive Manual provides guidelines for statistical offices and other agencies responsible for constructing CPIs, and explains in-depth the methods that are used to calculate a CPI. It also examines the underlying economic and statistical concepts and principles needed for making choices in efficient and cost-effective ways, and for appreciating the full implications of those choices.